2010
DOI: 10.1038/sj.bjc.6605823
|View full text |Cite
|
Sign up to set email alerts
|

ANO1 amplification and expression in HNSCC with a high propensity for future distant metastasis and its functions in HNSCC cell lines

Abstract: Background:Head and neck squamous cell carcinoma (HNSCC) is associated with poor survival. To identify prognostic and diagnostic markers and therapeutic targets, we studied ANO1, a recently identified calcium-activated chloride channel (CaCC).Methods:High-resolution genomic and transcriptomic microarray analysis and functional studies using HNSCC cell line and CaCC inhibitors.Results:Amplification and overexpression of genes within the 11q13 amplicon are associated with the propensity for future distance metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(141 citation statements)
references
References 56 publications
8
129
2
2
Order By: Relevance
“…149 There are several reports highlighting the importance of ANO1 in cancer cell metastasis, i.e., Shi and coworkers demonstrated a correlation between ANO1 overexpression and lymph node metastasis of ESCC and advanced clinical stage of cancers 157 and Ayoub and collaborators found that increased ANO1 expression correlates with increased risk of developing metastases in oral and head and neck squamous cell carcinomas. 139 In contrast, Shiwarshi and coworkers find that reduced ANO1 expression slows proliferation and allow metastatic progression and they suggest that ANO1 expression is a switch between growth and metastasis. 143 …”
Section: Migration and Metastasismentioning
confidence: 99%
See 3 more Smart Citations
“…149 There are several reports highlighting the importance of ANO1 in cancer cell metastasis, i.e., Shi and coworkers demonstrated a correlation between ANO1 overexpression and lymph node metastasis of ESCC and advanced clinical stage of cancers 157 and Ayoub and collaborators found that increased ANO1 expression correlates with increased risk of developing metastases in oral and head and neck squamous cell carcinomas. 139 In contrast, Shiwarshi and coworkers find that reduced ANO1 expression slows proliferation and allow metastatic progression and they suggest that ANO1 expression is a switch between growth and metastasis. 143 …”
Section: Migration and Metastasismentioning
confidence: 99%
“…147 Other studies, however, show that cell proliferation in certain cell types is unaffected by ANO1, e.g. ANO1 overexpression or knockdown do not affect proliferation in head and neck squamous cell carcinoma (HNSCC) 137,139 and ANO1 knockdown does not affect proliferation in pancreatic ductal adenocarcinoma cells. 120 ANO1 isoforms are shown to produce different channel characteristics (voltage and Ca 2C dependency).…”
Section: Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, downregulation of Ano1 contributes to cerebrovascular remodelling by promoting basilar smooth muscle cell proliferation, which is through inhibition of expression of cyclin D1 and cyclin E [26]. We performed additional experiments and compared proliferation of two HNSCC (CAL33, BHY) and one colonic epithelial cell line (HT 29 ) using an online impedance-based xCELLigence proliferation assay system [27] (figure 1a). Proliferation was clearly higher in the HNSCC cell lines (cf.…”
Section: Ano1 Is Located On the 11q13 Ampliconmentioning
confidence: 99%